Morphological Model and Visual Characteristic of Leaf, and Fruit of Citrus (Citrus sinensis) - Strayker Ali Muda; Benyamin Lakitan; Dora Fatma Nurshanti; Fitra Gustiar; Rofiqoh Purnama Ria; Fitra Fadhilah Rizar; Lya Nailatul Fadhilah (AGRIUM: Jurnal Ilmu Pertanian, 2023)
Citrus is a well-known horticultural plant and consumed. Leaf and fruit are important citrus organs as a fruiting plant. This is confirmed by the vitamin, antioxidant, and other chemical content of these organs which are beneficial for the human health. Understanding the model of both organs will facilitate the potential content, functional capacity and plant yield in non-destructive way. The study was aimed to determine morphological model and visual characteristic of leaf, and fruit of citrus. The study was conducted by comparing direct measurement and finding the relationship with selected predictors using several regression types (i.e. linear, linear with zero intercept, exponential, logarithmic, polynomial, polynomial with zero intercept and power). The observational sample consisted of 100 leaves and 13 fruits of citrus randomly collected from healthy, normal and productive plants. The results showed that leaf length (LL) × leaf width (LW) was the most reliable predictor using the linear regression with zero intercept (R2= 0.991; y= 0.604x; RMSE= 0.34). Meanwhile, fruit circumference (FC) has been shown cannot be used as a predictor in determining fruit weight as indicated by low reliability. Based on the visual approach, ripe citrus is shown by the yellowish-green color of the peel along with the orange color of the pulp. Furthermore, in the middle of the ripened fruit pulp, there are also white stringy stuff. In conclusion, LL × LW with zero intercept regression is demonstrated the most reliability model for leaf area, while fruit circumference could not represent fruit weight.